The Causal Relationship between Family Cohesion, Family Conflict, and School Satisfaction Mediated by Self-Efficacy among Female Elementary School Students - M. Hojjati; M. Sadeghi, Ph.D.; M. Abbasi, Ph.D.; A. Senobar (خانواده و پژوهش, 2021)
This research was undertaken to investigate the causal relationship between family cohesion, family conflict, and school satisfaction mediated by self-efficacy among female elementary school students. The statistical population of the study was comprised of all female 5th and 6th graders in Khorramabad in 2018-19 school year. For the purpose of sampling, random cluster sampling method was utilized and 300 students were selected. According to Hu and Bentler criteria (1999), 15 individuals were selected for each variable and 28 questionnaires were excluded due to incompleteness. Eventually, the sample size was reduced to 272. The instruments included the Family Environment Scale (Moos & Moos, 1986), Self-Efficacy Questionnaire for Children (Muris, 2001), and Multidimensional Students’ Life Satisfaction Scale (Huebner, 2001). Structural equation modeling was performed to analyze the data. The results revealed that family cohesion and family conflict were significantly correlated with school satisfaction. Test of mediation using bootstrapping established a significant mediating role of self-efficacy in the relationship between family cohesion, family conflict, and school satisfaction. In explaining the findings, it can be said that when children have a sincere perception of the relationship with their parents which is without control and protection and also have a cohesive family, they will experience the consequence of their actions by feeling both satisfaction and happiness in academic life and also by believing in their controllable ability to succeed in education. Because students with a strong sense of efficacy spend more effort and time working and studying, they have better academic outcomes and, as a result, greater school satisfaction.